PERSEPSI WISATAWAN TERHADAP PULAU BALI SEBAGAI DESTINASI WISATA RAMAH MUSLIM - Wiiasih, Ranti; Zamany, M. Alfin (Jurnal Syarikah : Jurnal Ekonomi Islam, 2023)
The island of Bali is a tourist destination where the majority of the population is Hindu. On the other hand, many Muslim tourists visit the island of Bali and need services that are in accordance with the needs and rules of a Muslim. The purpose of this study was to determine the level of Muslim friendliness in Bali Island and to analyse the factors that influence tourists' perception of Bali Island as a Muslim friendly tourist destination. This study used primary data with 100 respondents and analysed using descriptive statistics and logistic regression. The results of the study indicate that the factors that influence tourists' perceptions of Bali Island as a Muslim-friendly tourist destination are the availability of halal food and beverages, prayer facilities, and accommodation.